Image Construction of Ukrainians from Galicia and Bukovyna in Russian Empire Military Propaganda (1914 — 1917) - Катерина Біла (Науковий вісник Чернівецького національного університету імені Юрія Федьковича. Історія)
The article deals with the «image of Ukrainians» of Galicia and Bukovyna create by the Russian Empire military propaganda during the First World War, and establish the ideological reason behind it. During the First World War the Russian Empire military propaganda in accordance with its strategic tasks intentionally depicted Ukrainians of Galicia and Bukovyna as poor and primitive people who are, nevertheless, good natured and hard-working. The media presented them as «victims» and amplified this image over whole Ukrainian population; in particular, it was applied to the peasants of the Western Ukraine. By design of the propagandists and the occupation government, the peasantry had to become the social backbone of Empire’s warfare; its opinion was easy to manipulate by promising them land plots or abolition of taxes. Peasants’ living conditions, which were undermined by war and poverty, aroused sympathy among the caring citizens, whose emotions the propaganda targeted. The main goal of the Russian military propaganda included mobilization of the Empire’s population, both military and economic. That’s why the Empire’s media landscape kept instigating to defence of «brotherly» Slavic nations, including the «lesser Russian brothers», the term applied to the Ukrainians of Galicia and Bukovyna. Such slogans gradually created the rhetoric of «justified» and defensive war, participation in it was a matter of honour and dignity, any contribution, either in the battlefield or through economic support was considered a deed worthy of respect. The propaganda attempted to advocate to compassion to the population in the territories, occupied by the Russian army. Simultaneously, the Empire’s censorship avoided to underline the Ukrainian identity, using obscure term «Russians» towards the population of the Western Ukraine instead. The Russian Empire’s ideology refrained from considering Ukrainians as a separate nation, as they were equated to Russians by using «Ruthenian» as the common term. The journalists frequently used such terms as «Ruthenian» Galicians, «Ruthenian» population of Bukovyna, the region was additionally marked by such historic terms as «Carpathian Rus» or «Red Rus». Such propaganda materials shaped an image of «unity» between Russian and Ukrainian cultures, household manners, and national clothes to justify the Empire’s attempts to claim those lands. By additionally manipulating the Orthodoxy, the propaganda imposed an idea of spiritual unanimity between the Russians and Ukrainians. In this way it established an illusion that the Ukrainians and Russians never had conflicts, had common spiritual goals and values, and thus there were no any differences between them. This propaganda stroke — «identity construction» — was an efficient tool for political and cultural manipulations of the Russian Empire government. It helped to authorize the Empire’s demands for Ukrainian lands by imposing ideas of «unification» and illusions of the «single Russian nation».